2017
DOI: 10.1186/s12864-017-3584-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of the floral transition in Rosa chinensis ‘Old Blush’

Abstract: BackgroundThe floral transition plays a vital role in the life of ornamental plants. Despite progress in model plants, the molecular mechanisms of flowering regulation remain unknown in perennial plants. Rosa chinensis ‘Old Blush’ is a unique plant that can flower continuously year-round. In this study, gene expression profiles associated with the flowering transition were comprehensively analyzed during floral transition in the rose.ResultsAccording to the transcriptomic profiles, 85,663 unigenes and 1,637 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
(65 reference statements)
2
23
0
Order By: Relevance
“…This was much better than previously published data for these two species (Table 2 , Additional file 1 : Table S1, Additional file 2 : Table S2; Fig. 3 a) [ 18 , 20 , 26 , 27 ] and other species/materials in Rosa [ 19 , 21 , 22 , 28 ]. A further assembly with all available data for OB produced even better transcript N50 (2092 bp) and average length (1359 bp).…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…This was much better than previously published data for these two species (Table 2 , Additional file 1 : Table S1, Additional file 2 : Table S2; Fig. 3 a) [ 18 , 20 , 26 , 27 ] and other species/materials in Rosa [ 19 , 21 , 22 , 28 ]. A further assembly with all available data for OB produced even better transcript N50 (2092 bp) and average length (1359 bp).…”
Section: Resultsmentioning
confidence: 47%
“… 46.46 61 M 887 Yan et al 2016 [ 20 ] OB na 85,663 na na. 70 M 814 Guo et al 2017 [ 26 ] OB c 208,039 111,954 1997 45.8 231M c 1111 Han et al 2017 [ 27 ] Core set 1 BT vs. OB; 90% identity na. 10,773 2282 na.…”
Section: Resultsmentioning
confidence: 99%
“…A GO and KEGG pathway enrichment analysis indicated that the common DEGs between EV vs. ER and LV vs. LR were enriched for circadian rhythm -plant and salicylic acid biosynthetic process (Fig. S6b), indicating that circadian rhythm and salicylic acid play an important role in the B. napus oral transition, which was also reported in the Annona squamosa and Rosa chinensis [40,41]. We also observed signi cant enrichment for genes involved in the circadian rhythm between LR vs. ER, suggesting that the owering time difference between early-and late-owering lines was primarily due to the expression difference of circadian rhythm genes (Fig.…”
Section: Identi Cation Of Owering Degsmentioning
confidence: 62%
“…Most of the accumulated information on flowering time control involves changes at the transcriptional level (Guo et al ., ), but important post‐translational steps are also pivotal to this process (Swiezewski et al ., ; Posé et al ., ). CONSTANS protein is particularly sensitive to post‐translational modifications, with both phosphorylation (Sarid‐Krebs et al ., ) and ubiquitination (Valverde et al ., ) playing important roles in its stability.…”
Section: Introductionmentioning
confidence: 99%